Sandra Pasco COVID-19 Photograph of Stanford Hospital - Pasco, Sandra::::::::: (2022)
A photograph taken inside Stanford Healthcare Hospital at 500 Pasteur Drive in Palo Alto, California during the COVID-19 pandemic.